Double-Cross-Linked Networks Based on Methacryloyl Mucin - Olăreț, Elena (Polymers (Basel), 2021)
Mucin is a glycoprotein with proven potential in the biomaterials field, but its use is still underexploited for such applications. The present work aims to produce a synthesis of methacryloyl mucin single-network (SN) hydrogels and their double-cross-linked-network (DCN) counterparts. Following the synthesis of the mucin methacryloyl derivative, various SN hydrogels are prepared through the photopolymerization of methacrylate bonds, using reaction media with different pH values. The SN hydrogels are converted into DCN systems via supplementary cross-linking in tannic acid aqueous solution. The chemical modification of mucin is described, and the obtained product is characterized; the structural modification of mucin is assessed through FTIR spectroscopy, and the circular dichroism and the isoelectric point of methacryloyl mucin is evaluated. The affinity for aqueous media of both SN and DCN hydrogels is estimated, and the mechanical properties of the systems are assessed, both at macroscale through uniaxial compression and rheology tests and also at microscale through nanoindentation tests.